The interplay of StyR and IHF regulates substrate-dependent induction and carbon catabolite repression of styrene catabolism genes in Pseudomonas fluorescens ST - Rampioni, Giordano; Leoni, Livia; Pietrangeli, Biancamaria; Zennaro, Elisabetta (BMC microbiology, 2008)
Background In Pseudomonas fluorescens ST, the promoter of the styrene catabolic operon, P styA , is induced by styrene and is subject to catabolite repression. P styA regulation relies on the StyS/StyR two-component system and on the IHF global regulator. The phosphorylated response regulator StyR (StyR-P) activates P styA in inducing conditions when it binds to the high-affinity site STY2, located about -40 bp from the transcription start point. A cis -acting element upstream of STY2, named URE, contains a low-affinity StyR-P binding site (STY1), overlapping the IHF binding site. Deletion of the URE led to a decrease of promoter activity in inducing conditions and to a partial release of catabolite repression. This study was undertaken to assess the relative role played by IHF and StyR-P on the URE, and to clarify if P styA catabolite repression could rely on the interplay of these regulators. Results StyR-P and IHF compete for binding to the URE region. P styA full activity in inducing conditions is achieved when StyR-P and IHF bind to site STY2 and to the URE, respectively. Under catabolite repression conditions, StyR-P binds the STY1 site, replacing IHF at the URE region. StyR-P bound to both STY1 and STY2 sites oligomerizes, likely promoting the formation of a DNA loop that closes the promoter in a repressed conformation. We found that StyR and IHF protein levels did not change in catabolite repression conditions, implying that P styA repression is achieved through an increase in the StyR-P/StyR ratio. Conclusion We propose a model according to which the activity of the P styA promoter is determined by conformational changes. An open conformation is operative in inducing conditions when StyR-P is bound to STY2 site and IHF to the URE. Under catabolite repression conditions StyR-P cellular levels would increase, displacing IHF from the URE and closing the promoter in a repressed conformation. The balance between the open and the closed promoter conformation would determine a fine modulation of the promoter activity. Since StyR and IHF protein levels do not vary in the different conditions, the key-factor regulating P styA catabolite repression is likely the kinase activity of the StyR-cognate sensor protein StyS.